Container ship size and port relocation - Olaf Merk (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2018)
This paper analyses the impacts of ever-larger ships on location choices for new container ports and examines when relocation of a port makes sense. Most ports are located close to cities, but have difficulties expanding. A number of new container ports have been built further away from urban centres, and existing ports may at some point feel the pressure to relocate.
Keywords: 330